Monolingual Used on The Historical Sites in Dili, Timor-Leste: A Study of Linguistics Landscape - Antonio Constantino Soares (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2024)
Timor-Leste  which is further called (TL) is also well-known as a multilingual and multicultural country. Besides, Timor-Leste also has 32 local languages and 3 foreign languages such as Portuguese, Bahasa Indoenesia and English. Portuguese is used as the official language however, Bahasa Indonesia and English are used as  working languages. This research aimed to determine and to explore the predominant language used in historical sites in Dili. This is a qualitative research and the data were collected by using taking pictures technique with a mobile phone camera. After all the data were collected  then, they were analyzed by using qualitaive descriptive method. The Results in this research showed that there are 6  historical sites found in Dili. Tetum language is used as monolingual to describe and explain the brutal action done by the Indonesian Military during the Indonesian occupation in Timor-Leste.